Postdoc Working Group "Rethinking Accelerated Learning": Online Public Lecture 28 November 2024 (2025)
Under the theme ‘Accelerated Education Programmes for Out-of-School Young People in Africa’, on 28th November 2024, Ms. Miriam Tusiimire from War Child Canada and Ms. Fatu Yumkella from Dalan Development Consultants (Sierra Leone) presented various models of accelerated literacy programmes. Find out more about the Postdoc Working Group here: https://www.bayreuth-academy.uni-bayreuth.de/en/postdoc-working-groups/Rethinking-Accelerated-Learning/index.html